2016
DOI: 10.1038/tp.2016.141
|View full text |Cite
|
Sign up to set email alerts
|

Increased DNA and RNA damage by oxidation in patients with bipolar I disorder

Abstract: The mechanisms underlying bipolar disorder (BD) and the associated medical burden are unclear. Damage generated by oxidation of nucleosides may be implicated in BD pathophysiology; however, evidence from in vivo studies is limited and the extent of state-related alterations is unclear. This prospective study investigated for we believe the first time the damage generated by oxidation of DNA and RNA strictly in patients with type I BD in a manic or mixed state and subsequent episodes and remission compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 40 publications
4
26
0
2
Order By: Relevance
“…In particular, our PHEWAS results implicate a gene, EIF1AD , which has a wel-described role in response to oxidative stress 97 . Reduced expression of EIF1AD (eukaryotic translation initiation factor 1A domain containing; also known as haponin) in the DLPFC was associated with panic attacks, mixed states, and BD-I; in line with this, a recent study found increased RNA damage due to oxidative stress in individuals with BD-I and mixed states, compared to controls, and a decrease in levels of RNA damage after remission from an episode 84 . A large number of associations in our pathway analyses (Table 5) also point to mitochondrial methyltransferase pathways, endoplasmic reticulum function, mitochondrial function, and mitochondrion location.…”
Section: Discussionmentioning
confidence: 69%
“…In particular, our PHEWAS results implicate a gene, EIF1AD , which has a wel-described role in response to oxidative stress 97 . Reduced expression of EIF1AD (eukaryotic translation initiation factor 1A domain containing; also known as haponin) in the DLPFC was associated with panic attacks, mixed states, and BD-I; in line with this, a recent study found increased RNA damage due to oxidative stress in individuals with BD-I and mixed states, compared to controls, and a decrease in levels of RNA damage after remission from an episode 84 . A large number of associations in our pathway analyses (Table 5) also point to mitochondrial methyltransferase pathways, endoplasmic reticulum function, mitochondrial function, and mitochondrion location.…”
Section: Discussionmentioning
confidence: 69%
“…Thermal denaturation transitions corresponding to duplexes 1:5 -4:5 led to values that were equivalent (Figure 2A -70 °C). We initiated experiments using AMV-RT ( Figure 2B) to observe: 1) that the duplex where the template contains an I (2:5) enables the incorporation of dA while the analogous G-containing duplex (2:5) does not catalyze this process under the conditions described herein (lanes 15 and 5); 2) that the I-template exhibits lower incorporation selectivity between dC and dT than that observed on the G-template, which preferentially adds dC ( Figure 2C); 3) that the G-or I-containing templates enabled the incorporation of dT, while the 8-oxopurine analogues do not (Lanes 4, 14,9,19); and 4) that duplexes Figure 2D, lanes 26, 32, 38, 44). The results indicate that in the case of the canonical template strand (1), dCTP keeps adding up to the +4N-position (opposite one additional A and two Cs) stopping at a site where the enzyme encounters a U (lane 23).…”
Section: Resultsmentioning
confidence: 89%
“…On a different note, oxidative damage of RNA is a topic that has increasingly captured attention due to its potential role in the development/progression of disease. [14][15][16][17] Oxidized RNA has been shown to occur in various types of RNA including rRNA, 18 miRNA, 19 or mRNA, 20 and intracellular mechanisms in charge of diminishing the impact of oxidation have been reported. [21][22][23][24] Furthermore, the role of oxidative stress on viral pathogenesis 25 is a factor that could lead to interactions between reverse transcriptases and oxidatively damaged RNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial dysfunction and oxidative stress have increasingly been speculated to be involved in the pathophysiology of bipolar disorder supported by findings of alterations of oxidative stress marker levels in peripheral blood, particularly involving oxidative stress to DNA and RNA . Oxidative damage to RNA has been proposed as a novel disease mechanism contributing to medical diseases , and urinary levels of markers of RNA and DNA damage, which are considered more reliable than plasma levels , have been found altered in patients with bipolar disorder . Other lines of evidence implicate disturbances within the arachidonic acid cascade in bipolar disorder, supported by findings of altered gene expression in peripheral blood .…”
Section: Introductionmentioning
confidence: 99%